Leadership styles of Nurse Managers and Supervisors in Capacity Management Department, Al- Wakra Hospital - Devanesan, C.W.; Samuel, E.S. (University of Jaffna, 2022)
Leadership is an art and discipline of guiding, directing, motivating, and inspiring a group or organization toward the achievement of common goals. There are several different leadership styles exhibited by the leaders in a healthcare setting. Nurse managers should observe their own leadership styles and its effects on the work environment, they can adjust to a better leadership style. The study aimed to explore the nurse manager’s perceptions on leadership styles among the nurse managers at Al- Wakra Hospital. An observational, cross-sectional survey was conducted among eight nursing supervisors, five bed managers and seven case managers at the capacity management department of Al- wakra Hospital. The samples were selected by convenience sampling. The multifactor leadership questionnaire was used to assess the leadership styles. It was a 45-item self-report questionnaire that measures a full range of leadership behaviors and three outcomes through its 12 subscales. The collected data were tabulated and analysed using Statistical Package for Social Scientists-23. In terms of transformational leadership, results indicate that nursing supervisors frequently influenced their subordinates through the employment of all five critical strategies of transformational leadership: attributed idealized influence; behavioral idealized influence; inspirational motivation; intellectual stimulation and individualized consideration (mean 3.80). Also bed managers (mean 3.42) and case managers fairly often influenced their subordinates (mean 3.26) respectively. The results showed that nursing supervisors (mean 3.11), bed mangers (mean 3.21) and case mangers (mean 3.15) all perceived themselves to fairly often demonstrate transactional leadership factors - contingent reward and active management by perceptions respectively. Overall, the data showed that the nurse mangers perceived that they frequently and fairly often displayed transformational leadership styles. The finding of the study is providing information about the nurse manager’s perceptions of self, will provide direction for future leadership continuing education offerings and professional development.
Keywords: Leadership Styles; Nurse Mangers; Supervisors